2019
DOI: 10.1177/0018726719866250
|View full text |Cite
|
Sign up to set email alerts
|

Learning from supervisor negative gossip: The reflective learning process and performance outcome of employee receivers

Abstract: Workplace gossip is generally viewed as a deviant behavior that negatively affects the work outcomes of employees. However, we argue that this negative view is incomplete. Drawing on the cultural learning perspective of gossip and social learning theory, we examine how the job performance of employee receivers benefits from supervisor negative gossip through reflective learning. On the basis of multi-source, cross-sectional designs, Studies 1 and 2 consistently find that supervisor negative gossip facilitates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 80 publications
0
70
0
1
Order By: Relevance
“…Therefore, the present research revealed the influence of negative workplace gossip on another important group: gossip receiver, which is not only a useful supplement to negative workplace gossip research from the recipient's perspective, but also response the recalls for research from multiple perspectives. 10,11 The proposed theoretical framework provides an understanding of whether, why, and when negative workplace gossip affects the recipient's actions to implement workplace ostracism (sender-oriented). Second, the empirical results proved that negative workplace gossip can result in the gossip recipients implementing workplace ostracism behaviors against the gossip senders.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the present research revealed the influence of negative workplace gossip on another important group: gossip receiver, which is not only a useful supplement to negative workplace gossip research from the recipient's perspective, but also response the recalls for research from multiple perspectives. 10,11 The proposed theoretical framework provides an understanding of whether, why, and when negative workplace gossip affects the recipient's actions to implement workplace ostracism (sender-oriented). Second, the empirical results proved that negative workplace gossip can result in the gossip recipients implementing workplace ostracism behaviors against the gossip senders.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Second, most previous studies that from a gossip receiver perspective emphasized the learning effect of negative workplace gossip based on social learning theory. 11,12 Therefore, although this research emphasized the role of learning motivation in the recipient employees' response to negative workplace gossip, it also correspondingly ignored the psychological cognitive mechanism of employees' reaction to this gossip. Employees tend to make reasoned judgments based on their colleagues' behaviors, which then forms part of their psychological beliefs about these colleagues, 13 with these individual beliefs further affecting their evaluations of and behavioral responses to their colleagues.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations